Correlation of numeratic literacy and self efficacy of learning mathematics student’s SDIT MUTIARA INSANI BATAM - Shinta, Marisa; Gusmania, Yesi; Husna, Asmaul (CAHAYA PENDIDIKAN, 2023)
The purpose of this study is to find out the relationship of numeration literacy and self-efficacy skills with the learning outcomes of class V SDIT Mutiara Insani Batam students. This research is a quantitative research. The population in this study is all students of grade V SDIT Mutiara Insani Batam, which is as many as 54 students. Sampling is done with saturated sample technique where all students become samples in this study. Test instruments in this study used validity and reliability tests. Where the validity and reliability results are valid and reliable. Data analysis using simple linear regression and multiple linear regression with two free variables. The results of the analysis showed that: (1) There is a significant link between numeration literacy skills to the mathematical results of grade V SDIT Mutiara Insani Batam students with r_x1y = 0.638. (2) There is a significant connection between self-efficacy to the mathematical results of grade V SDIT Mutiara Insani Batam students with r_x2y = 0.046. (3) There is a significant link between numeration literacy and self-efficacy literacy ability to study mathematics of grade V SDIT Mutiara Insani Batam with R_2x1y = 0.638. Keywords : Mathematics Learning Outcomes, Numerical literacy skills, and Self efficacy.